Visible light-driven photocatalytic fuel cell for wastewater treatment and electricity conversion - Tong, Warren Meng Wei (2022)

(untitled)
Dyestuff wastewater has high concentrations of noxious pollutants that are harmful to the environment and well-being of living organisms. However, it has huge potential to be recycled and reused for non-potable water applications such as irrigation and cleaning after proper treatment due to its ever-increasing amount being released from the industries. Photocatalytic fuel cell (PFC) is a sustainable and green technology, which is capable of treating dyestuff wastewater through photocatalytic degradation process while simultaneously producing electricity. In this study, a PFC system using NiFe2O4/ZnO/Zn photoanode and CuO/Cu cathode was developed. The NiFe2O4/ZnO/Zn photoanode was synthesized through the electrodeposition-hydrothermal combined method, whereas the wet chemical method was used to fabricate CuO/Cu cathode. Characterization of the prepared photoelectrodes was done through analyses such as FESEM, EDX, FTIR, XRD, UV-Vis DRS, TPR, LSV, EIS and MS. The surface morphologies, elemental compositions, functional groups and crystalline phases of the photoelectrodes were identified. Apart from that, the band gap potential, photocurrent density, interfacial charge transfer, conduction band (CB) potential and valence band (VB) potential were determined for the photoanode. Through FESEM analysis, the ZnO was revealed as having a tree-like structure with size ranging from 310 nm to 5930 nm, whereas the NiFe2O4 particles exhibited granular shapes with size varying from 64 nm to 239 nm. The CuO on the Cu cathode demonstrated rod-like structures with size fluctuating from 91 nm to 392 nm. Several process parameters were studied and they proved to have profound influence on the performance of the PFC system. Under the optimum condition of 0.5 % NiFe2O4/ZnO/Zn photoanode, 0.5 M supporting electrolyte concentration and alkaline pH 10, 65 % colour removal efficiency was achieved for RhB dye solution. In the context of electricity generation, it achieved Voc, Jsc, and Pmax values of 637 mV, 0.1831 mA/cm2 and 0.0253 mW/cm2, respectively. Radical scavenging test was also conducted to determine the active radical species involved in the photodegradation process and Z-scheme photocatalytic mechanism was proposed. Subsequently, the COD mineralization study was successfully carried out and followed by recycling test. Furthermore, the effectiveness of the PFC in treating real industrial printing ink wastewater was evaluated under direct sunlight. Lastly, cost analysis was performed to analyse the real-life application of the PFC system.